Inventaires des services de santé en français dans l’Ouest canadien : entre improvisation et gouvernance : 2000‐2010 - Boily, Frédéric; Gagné, Learry (Revue Gouvernance, 2013)
La difficulté pour les communautés francophones en situation minoritaire au Canada d’obtenir des services de santé dans leur langue est bien connue. Le problème est encore plus criant dans l’Ouest canadien, défavorisé par une faiblesse démographique et une grande dispersion de la population par rapport à l’Est (surtout l’Ontario et le Nouveau-Brunswick). Dans ce contexte, la mobilisation des francophones pour la défense de leurs intérêts est essentielle. Ce projet porte sur les relations entre les gouvernements provinciaux de l’Ouest, le gouvernement fédéral et les groupes francophones minoritaires en matière de politique de santé. Nous proposons de nous concentrer sur les provinces de la Colombie-Britannique, de l’Alberta et de la Saskatchewan pour la période récente allant de 2000 à 2010. L’analyse porte principalement sur les facteurs en politique publique qui ont permis à ces groupes de revendiquer un certain nombre de services de santé. Nous établissons une relation entre la participation active du fédéral durant cette période, la participation plutôt passive des provinces, et la préférence pour les projets de santé publique où le fédéral a pu jouer un rôle sans empiéter sur les pouvoirs provinciaux.

Repérage et analyse de l'information sur la santé dans Internet : le cas des CLOSM dans la province de l'Alberta - Bowker, Lynne (Francophonies d'Amérique, 2009)
La présente étude examine, dans le contexte des langues officielles, quelques-uns des besoins insatisfaits des communautés de langue officielle en situation minoritaire (CLOSM) au Canada sur le plan de la santé. Nous présentons les résultats d’une analyse de l’information sur la santé offerte dans Internet aux francophones de l’Alberta. Nous avons procédé à une évaluation comparative de l’information sur la santé destinée à la population albertaine en français et en anglais dans Internet. En présentant les résultats, cette analyse compare le nombre de textes en français et en anglais et se penche sur la qualité de la langue des textes en français.

Talk COVID to me: Language rights and canadian government responses to the pandemic - Chouinard, Stéphanie; Normand, Martin (Canadian Journal of Political Science, 2020)
Since the COVID-19 outbreak, a gradual loosening of linguistic obligations in public institutions and governments has been observed in various jurisdictions in Canada. This article argues that in addition to legal requirements to provide minority language services, it is not justifiable for governments to suspend or curtail such services in an emergency situation, for reasons pertaining to public safety and public health. After performing a survey and analysis of government actions against their constitutional, legislative, and policy language obligations to highlight best practices and deficiencies, we discuss the policy implications of these actions. In conclusion, the article considers how governments could better uphold their language obligations in times of emergency.

Accès aux services de santé et d’interprète accompagnateur : l’expérience des communautés minoritaires à faible densité de francophones au Canada. Rapport de recherche-Projet INTACC - de Moissac, Danielle (Société Santé en français, 2016)

Access to health and interpreter-companion services – the experience of sparsely populated Francophone minority communities in Canada - de Moissac, Danielle (Société Santé en français, 2016)

Impact of language barriers on access to healthcare for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Healthcare management forum, 2017)
While there is strong international evidence that language barriers present obstacles to healthcare access, quality and safety, little research has been conducted on the experience of official language minorities in Canada. This multiple method research used on-line and paper-based surveys, combined with semi-structured individual interviews to explore the experience with access to care of Francophone minorities living in four Canadian provinces. The majority of Francophones surveyed reported limited access to French language services and described an environment where low importance is given to addressing language barriers within the health system. Even when services are available, the lack of services in French sometimes results in avoidance of care. Results confirm that many Francophones face similar barriers to care as other language minorities in Canada. Strategies to improve access for official language minorities are discussed.

Impact of language barriers on quality of care and patient safety for official language minority Francophones in Canada - de Moissac, Danielle; Bowen, Sarah (Journal of Patient Experience, 2019)
Introduction: The risks to patient safety and quality of care faced by members of linguistic minority groups have been well-documented. However, little research has focused on the experience of official language minorities in Canada. Methods: This multiple method study (online and paper-based surveys combined with semi-structured individual interviews with patients and interpreters-health navigators) explored the experience of minority Francophones living in 4 Canadian provinces. Results: Patients and interpreters-navigators described experiences where language barriers contributed to poorer patient assessment, misdiagnosis and/or delayed treatment, incomplete understanding of patient condition and prescribed treatment, and impaired confidence in services received. Reliance on Google Translate and ad hoc, untrained interpreters are commonly reported, in spite of evidence highlighting the risks associated with such practice. Conclusion: Increased awareness that the risks of language barriers apply to official language minorities is essential.

L’accès aux services de santé en français et leur utilisation en contexte francophone minoritaire. Rapport final - Forgues, Éric; Landry, Rodrigue (Institut canadien de recherche sur les minorités linguistiques et Société Santé en français, 2014)

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.